2008
DOI: 10.1021/bi800316z
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Protein Kinase CK2 Activity by Fragments of CFTR Encompassing F508 May Reflect Functional Links with Cystic Fibrosis Pathogenesis

Abstract: Deletion of F508 in the first nucleotide binding domain (NBD1) of cystic fibrosis transmembrane conductance regulator protein (CFTR) is the commonest cause of cystic fibrosis (CF). Functional interactions between CFTR and CK2, a highly pleiotropic protein kinase, have been recently described which are perturbed by the F508 deletion. Here we show that both NBD1 wild type and NBD1 ΔF508 are phosphorylated in vitro by CK2 catalytic α-subunit but not by CK2 holoenzyme unless polylysine is added. MS analysis reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
67
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(75 citation statements)
references
References 45 publications
8
67
0
Order By: Relevance
“…Furthermore, here we show that this effect of pharmacological CK2 inhibition applies not only to CFTR function as a chloride channel but also to the processing of wt CFTR. Indeed, our results show that CK2 activity is also essential for the successful processing (and membrane trafficking) of CFTR: this may involve direct phosphorylation of CFTR by CK2, previously shown to occur at S422 (26), or this effect may involve other targets of CK2 that relate to CFTR-associated proteins.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Furthermore, here we show that this effect of pharmacological CK2 inhibition applies not only to CFTR function as a chloride channel but also to the processing of wt CFTR. Indeed, our results show that CK2 activity is also essential for the successful processing (and membrane trafficking) of CFTR: this may involve direct phosphorylation of CFTR by CK2, previously shown to occur at S422 (26), or this effect may involve other targets of CK2 that relate to CFTR-associated proteins.…”
Section: Discussionmentioning
confidence: 60%
“…Previous observations evidenced that CK2 was able only to phosphorylate CFTR peptides corresponding to the sequence PGTIKENIIFGVSY 512 D EYRYR, provided that residue Y512 was replaced with phosphotyrosine (26), strongly suggesting the potential for hierarchical phosphorylation, i.e., an interaction between CK2 and SYK at S511, the CK2 consensus, depending on a negative charge at the adjacent tyrosine (26,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…they found that peptides encompassing the 500 -518 sequence of CFTR promote the phosphorylation of NBD1 by the holoenzyme in an F508-dependent manner while inhibiting its phosphorylation by the isolated CK2a. Of note, these peptides also perturb the interaction between the a and b subunits of CK2 [55]. Although the mechanism by which NBD1 interacts with CK2 is not fully understood, this rather complex CK2-CFTR association is the first described DF508-dependent CFTR-kinase interaction that provides a functional link in the most frequent form of cystic fibrosis.…”
Section: Membrane-associated Ck2 Substratesmentioning
confidence: 99%
“…It has been recently reported that the CK2 activity is modulated by specific fragments of the CFTR protein and it could reflect a functional link between CK2 and cystic fibrosis pathogenesis. 132 …”
mentioning
confidence: 99%